A 5k-vertex kernel for 3-path vertex cover - Xiao, Mingyu; Kou, Shaowei (Theoretical computer science, 2023)
A 3-path vertex cover in a graph is a vertex subset C such that every path of three vertices contains at least one vertex from C. The parameterized 3-path vertex cover problem asks whether a graph has a 3-path vertex cover of size at most k. We give a kernel of 5k vertices for this problem, improving the previously known bounds.